Bandgap Shrinkage and Charge Transfer in 2D Layered SnS2 Doped with V for Photocatalytic Efficiency Improvement. Issue 2 (20th November 2021) - Shelke, Abhijeet R.; Wang, Hsiao‐Tsu; Chiou, Jau‐Wern; Shown, Indrajit; Sabbah, Amr; Chen, Kuang‐Hung; Teng, Shu‐Ang; Lin, I‐An; Lee, Chi‐Cheng; Hsueh, Hung‐Chung; Liang, Yu‐Hui; Du, Chao‐Hung; et al.
Abstract: Effects of electronic and atomic structures of V‐doped 2D layered SnS2 are studied using X‐ray spectroscopy for the development of photocatalytic/photovoltaic applications. Extended X‐ray absorption fine structure measurements at V K ‐edge reveal the presence of VO and VS bonds which form the intercalation of tetrahedral OVS sites in the van der Waals (vdW) gap of SnS2 layers. X‐ray absorption near‐edge structure (XANES) reveals not only valence state of V dopant in SnS2 is ≈4 + but also the charge transfer (CT) from V to ligands, supported by V L α, β resonant inelastic X‐ray scattering. These results suggest V doping produces extra interlayer covalent interactions and additional conducting channels, which increase the electronic conductivity and CT. This gives rapid transport of photo‐excited electrons and effective carrier separation in layered SnS2 . Additionally, valence‐band photoemission spectra and S K ‐edge XANES indicate that the density of states near/at valence‐band maximum is shifted to lower binding energy in V‐doped SnS2 compare to pristine SnS2 and exhibits band gap shrinkage. These findings support first‐principles density functional theory calculations of the interstitially tetrahedral OVS site intercalated in the vdW gap, highlighting the CT from V to ligands in V‐doped SnS2 . Abstract : The interstitially tetrahedral O–V–S site in the vdW gap of V‐doped 2D SnS2 establishes the origin of the charge transfer mechanism between metal ion V 4+ 3 d and ligand O 2‐ 2 p /S 2‐ 3 p states and the decrease in the band gap by studying synchrotron‐based techniques and first‐principles density functional theory.